Optimization of protein enrichment of fruit peels by mixed culture of Phanerochaete chrysoporium and schizophyllum commune as animal feed supplements - Saheed, Olorunnisola Kola; Jamal, Parveen; Alam, Md Zahangir (University Putra Malaysia, 2017)
Optimization of the process conditions of mixed culture of bacidiomycete fungi for 11 improved protein enrichment of fruit peels is necessary to ease replication and 12 scale-up processes. Six-day fermentation period and temperature of 32°C were 13 optimum for elevated protein synthesis and enzyme activities (78.99 units/ml for 14 α-amylase and 0.36 units/ml for cellulase). A highly significant quadratic model 15 obtained from Face Centered Central Composite Design (FCCCD) described the 16 process optimization. Linear effect of pH and inoculum size were significant (p < 17 0.05) while pH and moisture content (MC) interact significantly. 70.2% MC, pH 18 5.4 and 6.1% inoculum were the optimum level for a maximum crude protein 19 synthesis of 198.77 mg/g. The crude protein contained essential and non-20 essential amino acid at a comparable level with other bioprocessed materials that 21 are currently used as animal feed supplement.